INDIVIDUALS CERTIFICATION SYSTEM AND ITS INSTITUTIONAL STRUCTURE (ACCREDITATION SYSTEM) EVALUATION IN LATVIA - Sarmite Jegere (European Scientific Journal, ESJ, 2015)
In the Latvian certification system of individuals there is necessary to ensure appropriate process realization in the public protection interests and government needs, which incorporates in EU common structure. Certification system and its institutional structure assessment is done with the aim to develop proposals for the improvement of Latvian certification system for reducing costs, while ensuring both high system efficiency and service recipients and the public interest. To achieve its goals study provided a summary of the situation in Latvia, as well as in the neighboring countries: Lithuania, Poland, Estonia and Finland. During the study, there were used both the secondary and the primary sources of information. Primary research was carried out in Latvia and consisted of two parts: expert interviews and focus groups. Results of the research are guidance to the overall approach and the criteria by which to guide in the future, for setting which professional service providers require a mandatory certification. In the process of study there is made a Matrix which helps to define certified profession, taking into account the need to protect the public interest and the level of national involvement in regulation of specific areas of professional services.